Asuhan Keperawatan Gerontik Pada Pasien Dengan Rheumatoid Arthritis Di Panti Sosialtresna Werdha Sabai Nan Aluih Sicincin Kabupaten Padang Pariaman - Dini Eka Putri; Sandra Dewi; Mike Asmaria; Armaita . (CV. ITTC INDONESIA, 2026)
The increasing number of elderly people causes an increase in the incidence of chronic diseases, one of which is rheumatoid arthritis which can reduce the quality of life. Data in the world shows that sufferers of joint disorders reach 81% of the population. In West Sumatra, it is recorded at around 8.50% of the population. Data obtained at PSTW Sabai Nan Aluih Sicincin, Padang Pariaman Regency, namely rheumatoid arthritis ranks first with a number of cases of 22 sufferers. The purpose of this case study is to be able to provide nursing care to Mr. M with Rheumatoid arthritis at PSTW Sabai Nan Aluih Sicincin, Padang Pariaman Regency. The research method used is a case study method with a nursing process approach that includes assessment, nursing diagnosis, intervention, implementation, and evaluation. The study was conducted at PSTW Sabai Nan Aluih Sicincin, Padang Pariaman Regency, the implementation time was from 11 to February 16, 2026. The results of the study obtained nursing problems, namely chronic pain, impaired physical mobility, and disturbed sleep patterns. Nursing interventions carried out included pain management, mobility support and sleep support. The implementation included providing non-pharmacological techniques to reduce pain, encouraging range of motion, and modifying the environment to increase comfort. Evaluations of chronic pain, impaired physical mobility, and disturbed sleep patterns were continued and accompanied by caregivers. The conclusion of this case study is that appropriate and continuous nursing care can help reduce pain, increase mobility, and improve the patient's sleep quality. Recommendations are aimed at patients to be able to independently perform non-pharmacological pain management techniques, perform simple mobilization independently, and take medication regularly as prescribed by the doctor. Caregivers are also advised to provide support, regular monitoring, and assistance in implementing optimal patient care.